THE RELATIONSHIP BETWEEN BODY MASS INDEX AND RISK OF ACUTE CORONARY SYNDROME IN PATIENTS WITH TYPE 2 DIABETES - Mohammed Mughabbish Thafrani; Mustafa Hussain Sabie; Mohammad Ahmed Motwwam; Abdullatif Alhassan Fathi; Abdullah Ali Shabani; Alhassan Hamood Derban (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Body mass index, the risk of cardiovascular events, and all-cause mortality are related in diabetics is a debatable matter.  Diabetes patients are more likely to experience cardiovascular complications. It is commonly known that obesity raises the risk of cardiovascular disease (CVD) in the general population. Little is known about the relationship between BMI and major adverse cardiovascular events, despite the fact that these are important health outcomes for individuals with diabetes. The connection between a person's BMI and mortality in those with diabetes has been the subject of continuous discussion. "Obesity paradox" in diabetics is often documented, suggesting that the mortality rates of individuals with diabetes who have elevated BMIs are lower than those of individuals whose BMIs are thought to represent normal weight.Aim of the Study: The purpose of the present review is to understand the relationship between body mass index (BMI) and cardiovascular complications like acute coronary syndrome in patients with Type -2 Diabetes.Methodology: The review is a comprehensive research of PUBMED from 1997 to 2023.Conclusion: Despite the debate, it is suggested that patients who do not receive insulin therapy and have type 2 diabetes mellitus also maintain the obesity paradox. The lowest and highest mortality rates were found in class I obese patients and the normal weight population, respectively, when examining the relationship between BMI and all-cause mortality in patients with type 2 diabetes mellitus and ACS. The benefit of obesity for survival was eliminated for patients on insulin therapy.